2011
DOI: 10.3732/ajb.1000231
|View full text |Cite
|
Sign up to set email alerts
|

How young trees cope with removal of whole or parts of shoots: An analysis of local and distant responses to pruning in 1‐year‐old apple (Malus ×domestica; Rosaceae) trees

Abstract: Pruning typically induced growth redistribution toward traumatic reiterations and enhanced growth of the remaining unpruned axes with a concomitant decrease of flowering and cambial growth. Although results could be interpreted in relation to the root-shoot balance, tree responses appeared highly cultivar-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
2
18
2
Order By: Relevance
“…In general, 2-year-old shoots in all pruning treatments developed proleptic shoots in every zone, except for the two basal zones in short-and intermediate-pruned shoots, and the three basal zones in long-pruned shoots. The lack of proleptic shoots in these basal zones comports with the concept of an acrotonic gradient being restored after pruning (Barlow and Hancock 1960;Mika 1986;Fumey et al 2011). Thus the proleptic shoot lengths decreased from the apical to the basal ends of the shoots, and therefore only spurs developed from the vegetative buds located in the basal zones.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In general, 2-year-old shoots in all pruning treatments developed proleptic shoots in every zone, except for the two basal zones in short-and intermediate-pruned shoots, and the three basal zones in long-pruned shoots. The lack of proleptic shoots in these basal zones comports with the concept of an acrotonic gradient being restored after pruning (Barlow and Hancock 1960;Mika 1986;Fumey et al 2011). Thus the proleptic shoot lengths decreased from the apical to the basal ends of the shoots, and therefore only spurs developed from the vegetative buds located in the basal zones.…”
Section: Discussionmentioning
confidence: 75%
“…Apical growth and axillary meristem fates are determined by the genetic background of trees, internal competition for resources and external limitations imposed by the environment. In the case of apical growth, which results from the initiation of new organs produced by the apical meristem (Barthélémy and Caraglio 2007), differences have been found among cultivars and the same cultivars growing on different rootstocks (Weibel et al 2003), as well as among horticultural practices applied to different species (Millard and Neilsen 1989;Berman and DeJong 1997;Fumey et al 2011). Axillary meristems (embryonic cells formed in the axils of the initiated leaf) may develop different fates (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stephan et al [7] analyzed the effect of pruning intensity on apple tree architecture and Gordon & Dejong [8] studied the effect of sprouts removal and fruit crop on P LS. Fumey et al [9], in a comprehensive experimental study, analyzed the consequences of different pruning practices on tree branching in apple trees. They found that pruning enhanced vegetative growth and decreased flowering, yet they did not provide a quantitative model to predict the consequences of different practices.…”
Section: Introductionmentioning
confidence: 99%